2018
DOI: 10.1161/jaha.118.009218
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Is Impaired and Relates to Cardiac Dysfunction in Patients With Atrial Fibrillation Both Before and After Successful Catheter Ablation

Abstract: BackgroundAtrial fibrillation (AF) is associated with myocardial infarction, and patients with AF and no obstructive coronary artery disease can present with symptoms and evidence of cardiac ischemia. We hypothesized that microvascular coronary dysfunction underlies these observations.Methods and ResultsMyocardial blood flow (MBF) at baseline and during adenosine stress and left ventricular and left atrial function were evaluated by magnetic resonance in 49 patients with AF (25 paroxysmal, 24 persistent) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
(38 reference statements)
1
31
0
2
Order By: Relevance
“…At the baseline scan, the CMR protocol included retrospectively ECG-gated time-resolved balanced steady-state free precession (bSSFP) cine imaging in horizontal long axis (‘four-chamber’) and vertical long-axis (‘two-chamber’), for the evaluation of left ventricular (LV) ejection fraction (LVEF) and volumes, and LA emptying function (LAEF) and volumes as previously described [ 18 , 19 ]. All images were analysed using cvi42 software (version 5.3.4, Circle Cardiovascular Imaging Inc, Calgary, Alberta, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…At the baseline scan, the CMR protocol included retrospectively ECG-gated time-resolved balanced steady-state free precession (bSSFP) cine imaging in horizontal long axis (‘four-chamber’) and vertical long-axis (‘two-chamber’), for the evaluation of left ventricular (LV) ejection fraction (LVEF) and volumes, and LA emptying function (LAEF) and volumes as previously described [ 18 , 19 ]. All images were analysed using cvi42 software (version 5.3.4, Circle Cardiovascular Imaging Inc, Calgary, Alberta, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental data in humans demonstrated that the raise in myocardial blood flow accompanying AF may be insufficient to compensate for the increased cardiac workload due to the AF-related rise in heart rate, differently to what happens to the same hearts during atrial pacing at similar ventricular rate [10]. In addition to this reduction in coronary blood flow due to the irregularity of the RR intervals, a recent work [34] suggests that an underlying microvascular dysfunction, strictly related to left ventricular and left atrial mechanical dysfunction, may play a role in myocardial blood flow impairment in AF patients. In a similar context, the present computational framework focuses on the effects that different ventricular rates exert on the coronary circle during AF.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal and multiparametric cardiac magnetic resonance studies show that even patients with apparently lone AF have significantly impaired ventricular myocardial energetics (figure 5), coronary microvascular dysfunction and subtle reduction in left ventricular performance, which fail to normalise following catheter ablation 32 46. This suggests that AF may actually be the consequence (rather than the cause) of an occult cardiomyopathy, which is unaffected by successful rhythm control, and that adjunctive therapies may be needed to target the ongoing drivers of the disease process.…”
Section: Beyond the Atrium: Is Af A Systemic Disease?mentioning
confidence: 99%